Metode Duduk Selingkar â€œHalaqah Taâ€™limâ€ Dalam Membimbing Kecerdasan Emosional Dan Spiritual Siswa (Studi Kasus Di MI Plus Al-Kautsar Sleman Yogyakarta) - Albadri, Rizqika Hamid (Educreative : Jurnal Pendidikan Kreativitas Anak, 2019)
This research result shows that model of Halaqoh Taâ€™lim is one of obligation programfollowed by all the students. Its goal is to harmonize theory in the classroom with theunderstanding and meaning. This halaqoh plan is implemented, among others, theimplementation of material and the division of teacher work as guidance teacher ortutor. In practice, halaqoh is done by forming small groups. The material is a dailyprayer, hadits, tarikh, and manners. The methods are discussions, assignments, sociodramas, telling stories, and habituation. Emotional intelligence and spiritualdevelopment of students at Al - Kauthar MI Sleman, Yogyakarta can be seen fromhonesty, responsibility, visionary, discipline, cooperation, fairness, and students caringin daily activities in the madrasah